The Market for Conflicted Advice - CHANG, BRIANA; SZYDLOWSKI, MARTIN (Journal of Finance, 2020)
ABSTRACT We present a model of the market for advice in which advisers have conflicts of interest and compete for heterogeneous customers through information provision. The competitive equilibrium features information dispersion and partial disclosure. Although conflicted fees lead to distorted information, they are irrelevant for customers' welfare: banning conflicted fees improves only the information quality, not customers' welfare. Instead, financial literacy education for the least informed customers can improve all customers' welfare because of a spillover effect. Furthermore, customers who trade through advisers realize lower average returns, which rationalizes empirical findings.